Content Analysis of Class X High School Physics Learning Video by Koh Ben on the Big Course YouTube Channel - Muh Fajrin Arifa; Restu Widiatmono; Jumadi Jumadi (Jurnal Penelitian Pendidikan IPA, 2023)
This paper reports research that aims to determine the feasibility of a learning video made by Koh Ben on the 'BIG Course' YouTube channel. Video learning is one of the most frequently used learning media and only videos that are appropriate can provide maximum benefits in learning physics. This study used a content analysis design with 4 analyzes carried out, namely content analysis, presentation analysis, graphic analysis, and language analysis. The learning videos analyzed were taken directly from the YouTube channel totaling 20 videos containing material for class X physics in the 2013 curriculum. From the results and discussion, it was concluded that the 20 videos for teaching physics for class X were very feasible with a percentage of 89.25% on the content aspect, 86% on the aspect delivery, 91.5% in the graphic aspect, and 99.75% in the language aspect